Panel data analysis for Sabah construction industries: choosing the best model - Fitrianto, Anwar; Kahal Musakkal, Nur Farhanah (Elsevier BV, 2016)
Analysis of panel data by using statistical models is rapidly growing. It is sometime tough for the novice users of panel data to make an informed choice of what estimators best suit their research questions. This paper is meant to find best model among few types of models such as panel data models and ordinary least squares (OLS) regression for Sabah construction industries. The best model will be chosen based on lowest Root Mean Square Errors (RMSE). The purpose of comparing between models is to find the most efficient model which will be useful for prediction. After analyzing the data using SAS software, it was found that two-way fixed effect panel data model provide the lowest RMSE for the Sabah construction industries.